2005
DOI: 10.1021/jp050095x
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Stimulated Raman Study of Excited-State Evolution in Bacteriorhodopsin

Abstract: Femtosecond time-resolved stimulated Raman spectroscopy (FSRS) is used to examine the photoisomerization dynamics in the excited state of bacteriorhodopsin. Near-IR stimulated emission is observed in the FSRS probe window that decays with a 400-600-fs time constant. Additionally, dispersive vibrational lines appear at the locations of the ground-state vibrational frequencies and decay with a 260-fs time constant. The dispersive line shapes are caused by a nonlinear effect we term Raman initiated by nonlinear e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
204
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(228 citation statements)
references
References 47 publications
21
204
3
Order By: Relevance
“…In ref. 18, the decay of the CϭC, C-C, and HOOP modes was determined to be 260 Ϯ 10 fs. The large mismatch in energy between these modes and the torsional modes would lead to an indirect impulsive excitation of the latter ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In ref. 18, the decay of the CϭC, C-C, and HOOP modes was determined to be 260 Ϯ 10 fs. The large mismatch in energy between these modes and the torsional modes would lead to an indirect impulsive excitation of the latter ones.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) These decay to low-frequency torsional modes on a sub-250-fs time scale (11,18), exciting a wave packet of torsional modes, while translocation of charge along the retinal chain occurs (19). (iii) The transition state, which corresponds to a twisted (but not isomerized) configuration of retinal (11), is impulsively generated (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Interestingly, Chen et al reported that for such systems the switching between conducting and non-conducting states appears to be related to the dihedral angles between the chromophores. 19,20 The photophysical properties of 1,4-bis(phenylethynyl) benzene (BPEB) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17] In the time-resolved experiments, three pulses are used: a Ͻ50 fs actinic pump pulse to excite the molecule to an upper electronic state, followed by stimulated Raman spectroscopy with an overlapping pair of ps Raman pump pulse, and a ϳ15 fs continuum probe pulse. It is possible to acquire spectra with time resolution of ϳ50 fs in the time delay between the actinic pump and probe pulses, and spectral resolution of Ͻ10 cm −1 due to the picosecond Raman pump pulse.…”
Section: Introductionmentioning
confidence: 99%